2017
DOI: 10.1039/c7ra10690d
|View full text |Cite
|
Sign up to set email alerts
|

Formation of intrinsic and silicon defects in MoO3 under varied oxygen partial pressure and temperature conditions: an ab initio DFT investigation

Abstract: DFT simulations predict how varied MoO3 preparation conditions could change intrinsic defect concentrations and avoid silicon contamination in photovoltaic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 89 publications
1
14
1
Order By: Relevance
“…We find these Poisson ratios to be negative, contradicting computational predictions. 35 It is quite common for anisotropic materials and especially 2D layered materials to exhibit negative Poisson's ratios in some directions due to their overall structure. 37,38 All other Poisson ratios are positive, as predicted, and the elastic stability conditions for an orthorhombic crystal 39 are satisfied for all four stiffness tensors, verifying that these are physically realizable solutions.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…We find these Poisson ratios to be negative, contradicting computational predictions. 35 It is quite common for anisotropic materials and especially 2D layered materials to exhibit negative Poisson's ratios in some directions due to their overall structure. 37,38 All other Poisson ratios are positive, as predicted, and the elastic stability conditions for an orthorhombic crystal 39 are satisfied for all four stiffness tensors, verifying that these are physically realizable solutions.…”
supporting
confidence: 57%
“…Modification of the tensor properties themselves is a separate question, expected to be important for thicknesses roughly on the order of 100 nm or less. MoO 3 is expected to have large elastic anisotropy, 35 with 9 distinct elastic constants (c ij ; Table 1) and 3 distinct refractive indices. Errors in the last displayed digit in each value are shown in parentheses.…”
mentioning
confidence: 99%
“…Indeed, research using the disappearing text paradigm (Rayner, Liversedge, White, & Vergilino-Perez, 2003), in which text is masked or disappears during a fixation, has shown that words can be encoded in as little as 50–60 ms. However, in the disappearing text paradigm, the eyes remain fixated on the word location even after it has disappeared, with this duration being modulated by word frequency (Blythe, Liversedge, Joseph, White, & Rayner, 2009; Liversedge et al, 2004; Rayner, Liversedge, & White, 2006). Furthermore, Rayner et al (2006) show that initial encoding of the word in parafoveal preview is vital in combination with the 60-ms foveal presentation.…”
Section: Introductionmentioning
confidence: 99%
“…The dipole nature of the α-MoO 3 layers is at the origin of its relatively high work function (WF) of about 6.5 eV [1,5]. Moreover, despite its insulator nature and high WF, previous studies pointed out that thin MoO 3 films may exhibit a conductive behavior in the presence of defects and oxygen vacancies [6][7][8][9][10] or via interaction with a metallic substrate such as copper [7].…”
Section: Introductionmentioning
confidence: 99%